Systematic Analysis of New Drug Indications by Drug‐Gene‐Disease Coherent Subnetworks - L Wang; Y Wang; Q Hu; S Li (Wiley, 2014)
Drug targets and disease genes may work as driver factors at the transcriptional level, which propagate signals through gene regulatory network and cause the downstream genes' differential expression. How to analyze transcriptional response data to identify meaningful gene modules shared by both drugs and diseases is still a critical issue for drug‐disease associations and molecular mechanism. In this article, we propose the drug‐gene‐disease coherent subnetwork concept to group the biological function related drugs, diseases, and genes. It was defined as the subnetwork with drug, gene, and disease as nodes and their interactions coherently crossing three data layers as edges. Integrating differential expression profiles of 418 drugs and 84 diseases, we develop a computational framework and identify 13 coherent subnetworks such as inflammatory bowel disease and melanoma relevant subnetwork. The results demonstrate that our coherent subnetwork approach is able to identify novel drug indications and highlight their molecular basis. CPT Pharmacometrics Syst. Pharmacol. (2014) 3, e146; doi:10.1038/psp.2014.44; published online 12 November 2014